Szkoły bernardyńskie na terenie Rzeczypospolitej Obojga Narodów w latach 1772–1864 - Sitnik, Aleksander Krzysztof (Biuletyn Historii Wychowania, 2019)
Between 1772 and 1864, the Bernardines ran in total 46 schools in the Polish-Lithuanian Commonwealth. Ten of them, at least in certain periods, were high schools (sub-departmental, district, secondary schools). A majority of the schools (24) were managed by monasteries in the Lithuanian Province. The successful development of Bernardine education in this territory should be attributed to the monks’ understanding of the need of spreading educationas well as to the relative political freedom in post-partition Lithuania. For that reason, educational activities could freely develop under the supervision of Adam Czartoryski, the Vilnius district superintendent and in the care of the Vilnius University. The well-developing education system of the Bernardines was destroyed by repressive measures applied by Nikolay Novosiltsev who replaced Czartoryski in 1823, and finally the tragic end of the November Uprising. Education in Podolia and Volhynia could be successfully developed owing to Tadeusz Czacki. The situation was different in the Kingdom of Poland where schooling was subjected to the Commission of National Education and the subsequent education authorities. Despite the hostile attitude towards monasteries, the Bernardines managed to run several schools. The most difficult situation was in Galicia which was incorporated by Austria after the Partitions of Poland and not under the beneficial influence of the Commission of National Education. A majority of Bernardine schools in Lithuania, just like in the Russian Province, survived the November Uprising. However, the subsequent restrictions imposed on political freedom had negative consequences for the standard of teaching. The dissolution of the monasteries put an end to the educational activity of the Bernardines in the five provinces in question. Most of the schools closed down as the monasteries were dissolved.